Efficacy of Resorbable versus Non Eugenol Packs in Enhancing Early Wound Healing following Gingival Excisional Procedures: A Randomised Controlled Study - Lakshmi Ramachandran; Anupama Tadepalli; Priyanka Cholan; Santo Grace Umesh; Harinath Parthasarathy; Chinmaya Agarwal (Journal of Clinical and Diagnostic Research)
Introduction: Conventionally, the raw wound after gingival excision is protected with non eugenol periodontal pack, in order to alleviate pain and preserve healing tissue which includes some potential disadvantages such as patient intolerance, pack loosening, speech difficulties and plaque accumulation. Aim: To clinically evaluate wound healing following the use of a resorbable periodontal dressing following gingival excisional procedures and to compare the outcomes with the conventional COE-PAKTM periodontal dressing. Materials and Methods: A randomised controlled trial was conducted in the Department of Periodontology, SRM Dental College, Chennai, Tamil Nadu, India from June 2022 to March 2023. Patients requiring gingival excision for gingival pigmentation, gummy smile correction and crown lengthening were included in this study, 36 patients in control group were treated with Laser assisted surgery followed by conventional COE-PAKTM and 36 patients in test group were treated with Laser assisted surgery protected with resorbable pack (RESO-PAC®). Wound healing scores (Landry’s scale) and patient comfort assessment {Visual Analogue Score (VAS)} was recorded at 7, 14 days following therapy. Data were analysed with IBM Statistical Packages for Social Sciences (SPSS) software 17.0 version using Independent t-test with level of significance 5%. Results: A total of 72 patients (38 males and 34 females) with a mean age range of 32.6 years were randomised into two study groups. Following the intervention, two participants in the test group and one subject in the control group could not report for the seven day follow-up and hence, the data of 69 participants, control (n=35) and test (n= 34) was used for final analysis. Both test and control groups showed satisfactory healing. Results in the test group were significantly better with respect to both wound healing and VAS assessment. Statistically significant difference was noted in the Wound Healing Index (WHI), VAS and Pain Intensity (PI) scores at the 7th and 14th day follow-ups (p<0.001). VAS and PI scores at 7th and 14th day (p<0.001). No of analgesics consumed during the first week were also significantly higher in the control group as compared to the test group (p<0.001**). Conclusion: RESO-PAC®, resorbable pack aided in wound healing following gingival excision and improved patient comfort during the initial healing phase. To add on the patients in the test group reported better compliance to the resorbable dressing and reported no adverse effects. Resorbable dressings could possibly facilitate secondary wound healing following surgical excision of gingiva.